The Puzzle of Moral Memory - Cowan, Robert (Journal of moral philosophy, 2020)
A largely overlooked and puzzling feature of morality is Moral Memory: apparent cases of directly memorising, remembering, and forgetting first-order moral propositions seem odd. To illustrate: consider someone apparently memorising that capital punishment is wrong, or acting as if they are remembering that euthanasia is permissible, or reporting that they have forgotten that torture is wrong. I here clarify Moral Memory and identify desiderata of good explanations. I then proceed to amend the only extant account, Bugeja’s (2016) Non-Cognitivist explanation, but show that it isn’t superior to a similar Cognitivist-friendly view, and that both explanations face a counterexample. Following this, I consider and reject a series of alternative Cognitivist-friendly explanations, suggesting that a Practicality-Character explanation that appeals to the connection between the practicality of moral attitude and character is superior. However, I conclude that support for this explanation should remain conditional and tentative.